2018
DOI: 10.1007/s11356-018-2683-x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and analysis of XCO2 in North China based on high accuracy surface modeling

Abstract: As an important cause of global warming, CO2 concentrations and their changes have aroused worldwide concern. Establishing explicit understanding of the spatial and temporal distributions of CO2 concentrations at regional scale is a crucial technical problem for climate change research. High accuracy surface modeling (HASM) is employed in this paper using the output of the CO2 concentrations from weather research and forecasting-chemistry (WRF-CHEM) as the driving fields, and the greenhouse gases observing sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Early studies of WRF‐VPRM development/application (Ahmadov et al, 2007; Ahmadov et al, 2009; Pillai et al, 2011) tested the system in a few case studies and with sparse tower measurements over small sub‐Europe domains. A few published studies (Diao et al, 2015; Feng et al, 2016; Liu et al, 2018; Park et al, 2018) have applied WRF‐VPRM to other continents. Diao et al (2015) evaluated WRF‐VPRM using surface CO 2 observations at three sites during a 5‐day period in 2010 over eastern China, and Liu et al (2018) evaluated WRF‐VPRM using the greenhouse gases observing satellite (GOSAT) retrieved column‐averaged CO 2 concentrations (XCO 2 ) over north China for 4 months in 2015; both Feng et al (2016) and Park et al (2018) applied WRF‐VPRM to the Southern California Air Basin, which is strongly affected by anthropogenic CO 2 emissions and less affected by biogenic CO 2 fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of WRF‐VPRM development/application (Ahmadov et al, 2007; Ahmadov et al, 2009; Pillai et al, 2011) tested the system in a few case studies and with sparse tower measurements over small sub‐Europe domains. A few published studies (Diao et al, 2015; Feng et al, 2016; Liu et al, 2018; Park et al, 2018) have applied WRF‐VPRM to other continents. Diao et al (2015) evaluated WRF‐VPRM using surface CO 2 observations at three sites during a 5‐day period in 2010 over eastern China, and Liu et al (2018) evaluated WRF‐VPRM using the greenhouse gases observing satellite (GOSAT) retrieved column‐averaged CO 2 concentrations (XCO 2 ) over north China for 4 months in 2015; both Feng et al (2016) and Park et al (2018) applied WRF‐VPRM to the Southern California Air Basin, which is strongly affected by anthropogenic CO 2 emissions and less affected by biogenic CO 2 fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the off‐line simulation cannot capture the real‐time feedback between synoptic weather and land‐surface dynamics and leads to large uncertainties in the simulated CO 2 fluxes/concentrations (Hu, 2008). Liu et al (2018) reported that surface CO 2 concentrations simulated with the WRF‐VPRM exhibited a similar trend with those observed at the Shangdianzi station in Beijing from February to May in 2015. In sum, long‐term simulations and observations of CO 2 fluxes/concentrations required to investigate and quantify CO 2 sources/sinks and budget in China are currently rarely reported (He et al, 2019; Thompson et al, 2016; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 58%
“…In previous research, the HASM has been successfully applied to simulate the distribution of soil properties (Shi et al, , ), carbon storage (Wang et al ., ; Yue et al, ) and XCO 2 (Zhang et al, , ; Liu et al, ) on global and regional scales. In a study on climate change, Zhao et al .…”
Section: Methodsmentioning
confidence: 99%
“…In previous research, the HASM has been successfully applied to simulate the distribution of soil properties (Shi et al, 2011(Shi et al, , 2016, carbon storage Yue et al, 2016) and XCO 2 Liu et al, 2018) on global and regional scales. In a study on climate change, Zhao et al (2017aZhao et al ( , 2017bZhao et al ( , 2018 introduced a HASM accompanied by GWR for temperature and precipitation simulations in China and in the Beijing-Tianjin-Heibei region, and great simulation results were achieved.…”
Section: The Hasmmentioning
confidence: 99%